'The essay method' a qualitative method for studying therapeutic dialogues. Issue 1 (3rd July 2019) - Varvin, Sverre
ABSTRACT: This paper presents a qualitative research method for analysing therapeutic dialogues called 'the essay method'. A central part of the method uses the format of the literary essay as a model. The method consists of a close monitoring of clinical material guided by an overall psychoanalytic/psychodynamic theoretical frame. It combines both clinical details and global patterns of clinical material and is especially fitted for studying relational qualities of psychotherapeutic dialogues. In this paper, the background for qualitative analysis in studying psychoanalytic material is discussed, and the procedures for using the method are demonstrated. A study of therapeutic competence in a group of student therapists is used as an example of the method in practice, demonstrating that the essay method may have potential for revising theory and establishing new concepts based on empirical findings. The essay method is compared with other qualitative methods, and it is argued that it is suitable for psychoanalytic research.